NATIONAL-CULTURAL CODE IN THE PARADIGM OF MODERN LINGUISTIC STUDIES - Domnich, O. (Linguistic and Conceptual Worldviews, 2019)
The article deals with the problem of the cultural code, typology of cultural codes and the nation- al-cultural code in the paradigm of modern linguistic studies. The definitions of these concepts are clarified and the significance of the national-cultural code research for such a multinational language phenomenon as the English language is substantiated. The study of the national-cultural code is deter- mined by the following reasons: the analysis of the formation and manifestation of national-cultural codes as the main representatives of the conceptual and national-specific worldview in the minds of polynational English speakers in various lingual areas of the world (such as North American, Australian-New Zealand, Asian and South African lingual and cultural areas), as well as the study of the problem of the correlation of universal characteristics with unique features (namely national-specific ones) in lingual and conceptual representation of the world in the discursive practices of representatives of various national-linguistic-cultural communities in the system of polynational multi-variety lingual phenomenon – the English language.
Keywords: cultural code, typology of cultural codes, national-cultural code, the polynational English language, the conceptual system